Attitudes Towards Spirituality and Other Worldly Experiences: An Online Survey of British Humanists. (15th August 2016) - Dein, Simon
This study examined attitudes towards and understandings of the term "spirituality" among members of the British Humanist Association (N = 318). Thirty-five percent agreed strongly and twenty-one percent moderately agreed that it was possible to be spiritual without being religious. Some respondents asserted that the term spiritual was so vague as to be almost useless. They preferred terms such as emotional connectedness, awe, or beauty, which are commonly included in definitions of spirituality. For a few individuals, spirituality referred to the existence of spirits. A minority in the study (12%) had what might be defined as 'other worldly experiences, ' although these were explained in purely naturalistic terms (e.g., lack of sleep, drugs/alcohol, and brain dysfunction). The primary conclusion from the survey is that many British Humanists see no contradiction between being a humanist and having experiences that are often defined as "spiritual."